Preparation of bactericidal PDMS surfaces by benzophenone photo-initiated grafting of polynorbornenes functionalized with quaternary phosphonium or pyridinium groups. (15th August 2021) - Lou, Yuzhen; Schapman, Damien; Mercier, Dimitri; Ceren Süer, N.; Eren, Tarik; Thebault, Pascal; Kébir, Nasreddine
Graphical abstract: Highlights: Design of bactericidal cationic PDMS surfaces by a 'grafting to' photo-process. Use of ROMP-synthesized polynorbornenes with phosphonium or pyridinium groups. The direct grafting was unsucessful. The grfating on thiolated surfaces led to charge densities above 10 14 charge/cm 2 . The grafted surfaces effectively kill surface bacteria. Abstract: Cationic ROMP-polymers bearing ammonium or phosphonium groups were photo-grafted onto a PDMS surface via the thiol-ene click reaction, in the presence of benzophenone. The PDMS surface was first thiolated using pentaerythritol tetrakis (3-mercaptopropionate) (PTTMP) under UV, in the presence of benzophenone. The obtained cationic surfaces exhibited charge densities above 10 14 charge/cm 2 and a higher degree of hydrophilicity compared to non-grafted surfaces. The live and dead tests performed by fluorescence microscopy revealed an effective contact bactericidal effect of these surfaces against Escherichia coli and Staphylococcus epidermidis .